Neuroblastoma IV-S with unfavorable clinical course. - Milano, A.; Cecinati, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Neuroblastoma is the commonest extracranial solid tumor in children. In its IV-S variant the skin metastases are frequent and may represent as in the case here reported the presentation sign of the tumor, in absence of whatever other clinically evident sign. Although the IV-S variant has a favorable clinical course towards the spontaneous regression in most cases starting after the first month of age but within the first year, in the case here reported, affecting a 7-month-old girl, the clinical course was complicated by neurological signs requiring chemotherapy.